Exploring Factors Contributing to Students’ Willingness to Communicate in English Class at The 11th Grade of Ma Nurul Islam Dasan Baru Murbaya Village Pringgarata Sub-District in The Academic Year 2022/2023 - Alfia Rahmawati Alfia Rahmawati; Syarifudin Syarifudin; Tuning Ridha Addhiny Tuning Ridha Addhiny (Cordova Journal, 2023)
This research is aimed to find out the students’ willingness to communicate (WTC) in English class, and unveil the factors that contribute to students’ willingness to communicate (WTC) in English class. This research implemented qualitative descriptive method by conducting observation and interview. The informants were the 11th grade students at MA Nurul Islam Dasan Baru. The findings showed that most students have medium willingness to communicate in English class. Meanwhile, less of them have high willingness to communicate in English class. Furthermore, the researcher found some factors contributing to students’ willingness to communicate (WTC), namely psychological factors and situational factors. Psychological factors include self-confidence, perceive communicate competence, learning anxiety, motivation, and personality. Meanwhile, situational factors include effect of task, effect of topics, teacher role, interlocutor, and classroom atmosphere.